The Influence of Financial Distress, Leverage, Company Growth, and Previous Year's Audit Opinion on the Going Concern Audit Opinion - Kadek Dinda Dyasnita; Ni Ketut Rasmini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The going concern audit opinion is a significant concern for auditors, investors, and other stakeholders as it relates directly to a company’s operational sustainability. This study aims to examine the influence of financial distress, leverage, company growth, and prior year audit opinion on the going concern audit opinion. The research was conducted on companies in the property and real estate, infrastructure, and transportation and logistics sectors listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample consists of 150 companies with 450 observational data obtained through purposive sampling. Logistic regression analysis was used to test the relationship between variables. The results show that financial distress and company growth have a negative effect on the going concern audit opinion, while the prior year’s audit opinion has a positive effect. Leverage has no significant effect. These findings are useful for companies to improve financial performance to reduce the risk of receiving a going concern opinion, and for auditors to consider financial and historical factors objectively.